ChemInform Abstract: Phosphino‐amine (PN) Ligands for Rapid Catalyst Discovery in Ruthenium‐Catalyzed Hydrogen‐Borrowing Alkylation of Anilines: A Proof of Principle. Issue 14 (March 2016) - Broomfield, Lewis Marc; Wu, Yichen; Martin, Eddy; Shafir, Alexandr
Abstract: A series of simple phosphino‐amine ligands is synthesized and screened in aromatic amine alkylations via ruthenium‐catalyzed hydrogen borrowing reactions.